SPATIAL AUTOCORRELATION ANALYSIS USING THE MORAN AND LISA INDEX ON THE SPREAD OF MALARIA DISEASE IN NORTH SUMATRA PROVINCE - Irana Putri Juliani; Hamidah Nasution (LPPM Universitas Bina Bangsa, 2024)
Malaria is a disease caused by protozoan infection of the Plasmodium genus, characterized by symptoms of alternating chills and prolonged fever. During the period of 2018-2022, the province of North Sumatra experienced an increase in malaria cases. This research aims to comprehend the spread of malaria cases in North Sumatra Province during that period through univariate analyses. This study uses secondary data obtained from the North Sumatra Provincial Health Office which includes the number of malaria cases. In the univariate analysis, the Moran's Index test revealed positive global spatial autocorrelation in 2021 and 2022, indicating inter-district/city connectivity and clustered patterns of malaria distribution in North Sumatra Province (I>E[I]). LISA analysis identified different clusters each year, but Hot Spots consistently occurred in Asahan Regency (2021-2022) and Batubara Regency (2022), while a Cold Spot persisted in South Tapanuli Regency for 3 years (2020-2022).